Association between social supports and negative emotions among pediatric residents in China: The chain-mediating role of psychological resilience and burnout - Song, Chao; Du, Xiao-Tian; Hong, Yun-Xia; Mao, Jian-Hua; Zhang, Wen (Frontiers in Public Health, 2023)
Background Chinese pediatricians are facing challenges, and there is a need to examine the issue of negative emotions, namely, stress, anxiety and depression, among front-line pediatric residents in clinical settings. Understanding the current situation and influencing factors of negative emotions among pediatric residents in China and exploring the formation mechanism can lay a foundation for psychological interventions. Methods A total of 138 pediatric residents in the Children's Hospital, Zhejiang University School of Medicine, China, were surveyed using the Depression Anxiety Stress Scale-21 (DASS-21), Social Support Rating Scale (SSRS), Connor-Davidson Resilience Scale (CD-RISC), and Maslach Burnout Inventory-General Survey (MBI-GS). Results (1) The incidence of abnormal stress, anxiety, and depression among pediatric residents was 18.8%, 47.8%, and 47.8% respectively. (2) Negative emotions were significantly negatively correlated with social supports and psychological resilience, and positively correlated with burnout. (3) The chain-mediating effect of resilience and burnout between social supports and negative emotions was significant. Conclusion Psychological resilience and burnout played a chain-mediating role between social supports and negative emotions. Measures should be taken to improve the mental health of Chinese pediatric residents.